2016
DOI: 10.4172/2155-9597.1000279
|View full text |Cite
|
Sign up to set email alerts
|

Human Mycobiota-Selected Ontocenoses of Students of Natural Science and Medicine

Abstract: Objectives: The aim of this study was to compare the prevalence of yeast-like fungi and yeasts on the mucous membranes of a group of students of Natural Sciences and Medicine. Materials and methods:The study involved 156 students of the Faculty of Biology and Biotechnology (FB&B) and 37 students of the Faculty of Medical Sciences (FMS). Material samples were collected with sterile cotton swab from the nose, mouth and throat. The identification of fungi was carried out by the evaluation of macrocultures and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A recent study conducted in Iran revealed K. marxianus as the second major nonalbicans Candida isolated from the oral cavity of 150 Iranian patients suffering from haematological malignancies [39]. Gorlaska et al [40], stated that K. marxianus as one of the leading non-C. albicans yeasts isolated from students in the faculty of Medical Science. The forth branch performed a close relation between both ITSF1 and ITSF3 strains with 99% identity with MN371880.1 P. kluyveri respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Iran revealed K. marxianus as the second major nonalbicans Candida isolated from the oral cavity of 150 Iranian patients suffering from haematological malignancies [39]. Gorlaska et al [40], stated that K. marxianus as one of the leading non-C. albicans yeasts isolated from students in the faculty of Medical Science. The forth branch performed a close relation between both ITSF1 and ITSF3 strains with 99% identity with MN371880.1 P. kluyveri respectively.…”
Section: Discussionmentioning
confidence: 99%